Renin-Angiotensin System and Sex Differences in COVID-19: A Critical Assessment - Chappell, Mark C. (Circulation research, 2023)
The current epidemic of corona virus disease (COVID-19) has resulted in an immense health burden that became the third leading cause of death and potentially contributed to a decline in life expectancy in the United States. The severe acute respiratory syndrome-related coronavirus-2 binds to the surface-bound peptidase angiotensin-converting enzyme 2 (ACE2, EC 3.4.17.23) leading to tissue infection and viral replication. ACE2 is an important enzymatic component of the renin-angiotensin system (RAS) expressed in the lung and other organs. The peptidase regulates the levels of the peptide hormones Ang II and Ang-(1–7), which have distinct and opposing actions to one another, as well as other cardiovascular peptides. A potential consequence of severe acute respiratory syndrome-related coronavirus-2 infection is reduced ACE2 activity by internalization of the viral-ACE2 complex and subsequent activation of the RAS (higher ratio of Ang II:Ang-[1–7]) that may exacerbate the acute inflammatory events in COVID-19 patients and possibly contribute to the effects of long COVID-19. Moreover, COVID-19 patients present with an array of autoantibodies to various components of the RAS including the peptide Ang II, the enzyme ACE2, and the AT 1 AT 2 and Mas receptors. Greater disease severity is also evident in male COVID-19 patients, which may reflect underlying sex differences in the regulation of the 2 distinct functional arms of the RAS. The current review provides a critical evaluation of the evidence for an activated RAS in COVID-19 subjects and whether this system contributes to the greater severity of severe acute respiratory syndrome-related coronavirus-2 infection in males as compared with females.